Circulation Enrichment of Functional Endothelial Progenitor Cells by Infantile Phototherapy. Issue 2 (21st July 2016) - Siavashi, Vahid; Asadian, Simin; Sharifi, Azam; Esmaeilivand, Masoumeh; Norouzinia, Roohangiz; Azadbakht, Mohammad; Nassiri, Seyed Mahdi
ABSTRACT: Phototherapy is the most common therapy used for severe jaundice. There is increasing evidence that phototherapy can directly affect the expression and function of cell surface receptors including adhesion molecules, cytokines, and growth factor receptors. In this study, the effect of two infantile phototherapy regimens, including single and intensive phototherapy was investigated on biological features of circulation endothelial progenitor cells (cEPCs), as well as on serum secretion of two important chemotactic cytokines, SDF‐1 and VEGF. Sixty infants diagnosed with severe hyperbilirubinemia and exposed to phototherapy were enrolled in this study. cEPCs were isolated before and after phototherapy and then migratory, proliferative, tubulogenic, and functional properties of these cells were analyzed. Our results revealed that intensive phototherapy markedly increased the release of EPCs into the circulation, and augmented the serum concentrations of both SDF‐1 and VEGF cytokines. Cell proliferation, tubulogenic, and migratory properties of cEPCs isolated and expanded from infants with intensive phototherapy were significantly improved. cEPCs from infants with intensive phototherapy also showed greater levels of acetylated low‐density lipoprotein and lectin binding. Overall, our results showed that the intensive phototherapy regimen can mobilize functional EPCs into the circulation through up‐regulation of serum levels of VEGF and SDF‐1, indicating phototherapy as an effective modality for improvement of stem cell mobilization in the therapeutic regenerative medicine. J. Cell. Biochem. 118: 330–340, 2017. © 2016 Wiley Periodicals, Inc. Abstract : The aim of this study was to evaluate the effect of single and intensive phototherapy on circulating EPCs in the peripheral blood of jaundice neonates.